Transition duration of ingested deuterium oxide to eccrine sweat during exercise in the heat. (January 2017) - Church, Adam; Lee, Fanny; Buono, Michael J.
Abstract: The time necessary for the initial appearance of ingested water as sweat during exercise in the heat remains unknown. Based on the current literature, we estimated fluid transition through the body, from ingestion to appearance as sweat, to have a minimum time duration of approximately three minutes. The purpose of this study was to test this prediction and identify the time necessary for the initial enrichment of deuterium oxide (D2 O) in sweat following ingestion during exercise in the heat. Eight participants performed moderate intensity (40% of maximal oxygen uptake) treadmill exercise in an environmental chamber (40 °C, 40% rH) to induce active sweating. After fifteen minutes, while continuing to walk, participants consumed D2 O (0.15 ml kg −1 ) in a final volume of 50 ml water. Scapular sweat samples were collected one minute prior to and ten minutes post-ingestion. Samples were analyzed for sweat D2 O concentration using isotope ratio mass spectrometry and compared to baseline. Mean±SD ∆ sweat D2 O concentration at minutes one and two post-ingestion were not significantly higher than baseline (0 min). Minutes three (9±3 ppm) through ten (23±11 ppm) post-ingestion had ∆ sweat D2 O concentrations significantly (P<0.05) higher than baseline. Such results suggest that ingested water rapidly transports across the mucosal membrane of the alimentary canal into the vasculature space, enters the extravascular fluid, and is actively secreted by the eccrine sweat glands onto the surface of the skin for potential evaporation in as little as three minutes during exercise in the heat. Highlights: We hypothesized rapid movement of water following ingestion to incorporation as sweat. We found three minutes as the minimum duration required for ingested D2 O to initially appear as secreted sweat. These data suggest that fluid transition, from ingestion to appearance as sweat, is much faster than data in the current literature.